2021
DOI: 10.1002/aenm.202100177
|View full text |Cite
|
Sign up to set email alerts
|

2D Covalent‐Organic Framework Electrodes for Supercapacitors and Rechargeable Metal‐Ion Batteries

Abstract: Covalent‐organic frameworks (COFs) represent a new frontier of crystalline porous organic materials with framework structures in 2D or 3D domains, which make them promising for many applications. Herein, the fundamental structural design aspects of 2D‐COFs are reviewed, which position them as suitable electrodes for electrochemical energy storage. The ordered π–π stacked arrangement of the organic building blocks in juxtaposed layers provides a pathway for efficient electronic charge transport; the 2D structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 159 publications
2
102
0
Order By: Relevance
“…However, by virtue of their large compositional diversity, some 2D organic materials can store charge through EDL capacitive [1289][1290][1291] and insertion pseudo-capacitive behaviour as well 1292 . Furthermore, 2D MOFs and COFs as a novel class of porous crystalline organic materials can be directly applied for capacitive energy storage 1293 , or as sacrificial templates for resulting sulfide/ carbon CoSNC 1294 and porous carbon 1295 for supercapacitor electrodes.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…However, by virtue of their large compositional diversity, some 2D organic materials can store charge through EDL capacitive [1289][1290][1291] and insertion pseudo-capacitive behaviour as well 1292 . Furthermore, 2D MOFs and COFs as a novel class of porous crystalline organic materials can be directly applied for capacitive energy storage 1293 , or as sacrificial templates for resulting sulfide/ carbon CoSNC 1294 and porous carbon 1295 for supercapacitor electrodes.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…As revealed, the high ID/IG ratio for the A-PVP-NC (1.18) and PI-NC (1.13) could be attributed to the presence of heteroatoms (i.e., N and O) and less crystallinity as evidenced by PXRD patterns. Furthermore, the corresponding Raman spectra were sequentially deconvoluted into four peaks (labeled peaks (1)-( 4)) since the integrated area ratio of sp 3 to sp 2 (Asp 3 /Asp 2 ) has been demonstrated to deliver helpful information about the nature of carbon, for example, a low Asp 3 /Asp 2 ratio indicates that a large amount of carbon exists as the sp 2 type [39,40]. As depicted, the peaks of ( 2) and ( 4) are related to sp 2 -type carbon, while the others are associated with sp 3 -type carbon.…”
Section: Characterizations Of A-pvp-nc and Pi-ncmentioning
confidence: 99%
“…Furthermore, scientists have developed numerous EES devices to store more energy with a long-life cycle. Among the existing EES devices, there is a complementary relationship between metal-ion batteries (MIBs) and supercapacitors (SCs) since the former has a high energy density, but the latter can deliver extreme power density [1][2][3][4][5]. It is recognized that increasing the power energy of the MIBs to as high as that of the SCs is intrinsically challenging, owing to the insertion/extraction of the metal ions from the corresponding electrode materials being principally essential, that is, the energy storage mechanism [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…3c) with the theoretical maximum based on their loading in the electrode. 6,10 The calculations (section S5, ESI †) indicated that 42% triphenylstibine units were accessed during the electrochemical process, which is much higher than that (12%) in microstructured Phos-COF. Considering the following points, (i) Sb-COF and Phos-COF have similar backbone and porous structure including BET surface area and PXRD pattern; 12 (ii) triphenylstibine and triphenylphosphine exhibit similar redox behaviour (CV in Fig.…”
mentioning
confidence: 99%
“…The conductive components can effectively create a synergistic effect (simultaneously as a scaffold) with the parent COF via reducing the resistance and enhancing the Faraday current between the electrode and the electrolyte. However, the introduction of conductive component usually leads to (i) the decrease in pore volume or specific surface area originated from the pore blockage, therefore the pore surface of COF material cannot be fully utilized; 6 (ii) the loss of COF crystallinity and thus the destruction of effective ion transport pathways. The other strategy is to introduce, usually via a bottom-up synthetic strategy, redox-active groups that could provide additional pseudocapacitor behaviour on the basis of electrochemical double-layer capacitor (EDLC) behaviour.…”
mentioning
confidence: 99%